Pengaruh Penambahan Tepung Kulit Kentang (Solanum tuberosum l) pada Pakan Terhadap Berat Karkas dan Persentase Karkas Burung Puyuh (Coturnix coturnix japonica) - Muhammad Ikbal; Semaun, Rahmawati; Novieta, Intan Dwi; Fitriani, Fitriani (Universitas Islam Negeri Alauddin Makassar, 2024)
Potato skins contain a lot of insoluble fiber, which can stimulate the digestive tract and make bowel movements more regular.This study aims to determine how the effect of adding potato skin flour (Solanum tuberosum) to quail feed on carcass weight and carcass percentage as alternative feed using the group random design method (RAK) with four treatments five repeats P0: No Control Treatment 0%, P1 Potato skin flour (Solanum tuberosum) 3% in feed, P2: Potato skin flour (Solanum tuberosum) 6% in feed, P3 : Potato skin flour (Solanum tuberosum) 9% in feed. The results of this study showed that the addition of potato skin starch (Solanum tuberosum) had no real effect (P>0.05) on carcass weight and quail carcass percentage. The average weight of the carcass is, P0 (112.7 gr/head), P1 (112.96 gr/head), P2 116.1 gr/head) and P3 (112.34 gr/head) and the average percentage of carcass, namely, P0 (64.946 gr/head), P1 (65.3704 gr/head), P2 (69.396 gr/head), and P3 (69.644 gr/head). The best treatment on carcass weight is in P2 treatment with the addition of potato skin flour (Solanum tuberosum) as much as 6% and the percentage of carcass is in P3 treatment